ORFeome Cloning and Systems Biology: Standardized Mass Production of the Parts From the Parts-List - Brasch, Michael A.; Hartley, James L.; Vidal, Marc (Genome Research, 2004)
Together with metabolites, proteins and RNAs form complex biological systems through highly intricate networks of physical and functional interactions. Large-scale studies aimed at a molecular understanding of the structure, function, and dynamics of proteins and RNAs in the context of cellular networks require novel approaches and technologies. This Special Issue of Genome Research features strategies for the high-throughput construction and manipulation of complete sets of protein-encoding open reading frames (ORFeome), gene promoters (promoterome), and noncoding RNAs, as predicted from genome and transcriptome sequences. Here we discuss the use of a recombinational cloning system that allows efficiency, adaptability, and compatibility in the generation of ORFeome, promoterome, and other resources.